Correlation between anthropometric measurements and activity level on length and diameter of semitendinosus tendon autograft in knee ligament surgery: A prospective observational study - Goyal Tarun (SICOT-J, 2020)
Introduction: Preoperative estimation of graft parameters can be useful while using hamstring grafts in knee ligament surgeries. Anthropometric parameters may be an easy way to predict the length and diameter of hamstring tendons. A prospective study was conducted to find the correlation between different anthropometric parameters and activity level of the patient on the length and diameter of the graft. Separate regression equations for males and females were also derived for easy prediction. Methods: Data were obtained from 95 patients who underwent arthroscopic anterior cruciate ligament reconstruction with autologous hamstring tendon graft. Variables studied were age, sex, height, weight, body mass index (BMI), thigh circumference, thigh length, Tegner activity level, diameter (double and quadruple) and length of semitendinosus tendon graft. Results: Height of the patient had strong correlation with graft length (r = 0.41, p < 0.001), double diameter (r = 0.29, p = 0.008) and quadruple diameter (r = 0.3, p = 0.006). Weight of the patients had strong positive correlation with graft length (r = 0.34, p = 0.002) and quadruple diameter (r = 0.34, p = 0.002). Thigh length was found to be positively correlating with graft length (r = 0.43, p < 0.001), double diameter (r = 0.29, p = 0.007) and quadruple diameter of graft (r = 0.34, p = 0.002). BMI and thigh circumference of the patients were not found to correlate with graft size. Male patients were found to have longer semitendinosus graft and larger double and quadruple diameter of the graft. There was no association between the Tegner activity scale and graft size. Regression equations between graft length and quadruple diameter and the anthropometric parameters are also derived. Conclusion: Height, weight and thigh length are useful anthropometric parameters in the prediction of hamstring tendon size. However, the patient’s Tegner activity level was not found to be associated with size of the hamstring tendon.